THE INFLUENCE OF RELIGIOSITY AND PEERS ON ACADEMIC DISHONESTY OF STUDENTS AT THE DEPARTMENT OF ECONOMIC EDUCATION, PADANG STATE UNIVERSITY: Pengaruh Religiusitas dan Teman Sebaya Terhadap Academic dishonesty Mahasiswa Departemen Pendidikan Ekonomi Universitas Negeri Padang - Yanni Eliza; Dessi Susanti (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This research aims to determine the influence of religiosity and peers on academic dishonesty students at the Department of Economic Education, Faculty of Economics and Business, Padang State University. The type of research used is Quantitative Descriptive. The population in this study were active students of the Department of Economic Education, Faculty of Economics and Business, Padang State University, class 2019-2022. Non – sampling method Probability Sampling. The sampling technique used is Purposive Sampling, Data collection was carried out by distributing questionnaires directly and through google form. Questionnaires were distributed to 80 students of the Department of Economic Education, Faculty of Economics and Business, Padang State University. The data analysis technique used was multiple linear regression analysis using SPSS 21. The results of this study show that there is an influence of the variables religiosity and peers significantly towards academic dishonesty to students of the Department of Economic Education, Faculty of Economics and Business, Padang State University. The results of the F test simultaneously show that religiosity and peers together have a significant effect on academic dishonesty. The coefficient of determination value shows that religiosity and peers are able to influence the dependent variable, namely academic dishonesty amounting to 35.6%.